The older adult psychotherapy treatment planner - Frazer, Deborah W. (Deborah Willets); Hinrichsen, Gregory A., 1951-; Jongsma, Arthur E., Jr., 1943- (Hoboken, N.J. : John Wiley & Sons, Inc., 2011)
'Like its predecessor, The TheraScribe Older Adult Psychotherapy Treatment Planner, Second Edition provides clinicians all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payers, and state and federal agencies. In addition, this new edition has been thoroughly updated to include empirically supported, evidence-based treatment interventions for older adults with mental disorders. Geropsychologists, social workers, counselors, and other mental health professionals will appreciate the clear format of this timesaving resource' --Provided by publisher.
Machine generated contents note: PracticePlanners{u04E5}ries Preface -- Acknowledgments -- Introduction -- Sample Treatment Plan -- Activities of Daily Living (ADL/IADL) Deficits -- *Anxiety -- *Caregiver Distress -- Communication Deficits -- Decisional Incapacity -- *Depression -- *Disruptive Behaviors of Dementia -- Driving Deficit -- Elder Abuse and Neglect -- *Falls -- *Grief Unresolved -- *Interpersonal Disputes -- *Life Role Transition -- *Loneliness/Interpersonal Deficits -- *Mania/Hypomania -- Medical/Medication Issues Unresolved -- Memory Impairment -- Nutritional Deficits Unresolved -- *Obsessive-Compulsive Disorder (OCD) -- *Panic/Agoraphobia -- Paranoid Ideation -- *Persistent Pain -- *Phobia -- Residential Issues Unresolved -- Sexually Inappropriate Behavior -- *Sleep Disturbance -- Somatization -- Spiritual Confusion -- *Substance Abuse/Dependence -- *Suicidal Ideation/Behavior -- Appendix A: Bibliotherapy Suggestions -- Appendix B: Professional References for Evidence-based Chapters -- Appendix C: Recommended Assessment Measures for Non-Evidence-based Chapters -- Appendix D: Index of DSM-IV Codes Associated with Presenting Problems -- * Indicates that selected Objective/Interventions are consistent with those found in evidence-based treatments.
Includes bibliographical references and index.
Keywords: Geriatric psychotherapy; Psychotherapy for older people; Mental illness -- Treatment -- Planning; Geriatric Psychiatry -- organization & administration; Patient Care Planning; Aged; Mental disorders -- Therapy; Psychotherapy -- methods